2020
DOI: 10.1272/jnms.jnms.2020_87-501
|View full text |Cite
|
Sign up to set email alerts
|

Association of Respiratory Tract Infection after Gastroenterological Surgery with Postoperative Duration of Hospitalization and Medical Expenses: Subanalysis of Data from a Multicenter Study

Abstract: Background Postoperative infections may be classified as surgical site infections developing within surgical sites or remote infections developing in areas outside the surgical site. Postoperative respiratory tract infections (PRTI) are a type of remote infection, and may be associated with a prolonged hospitalization period and increased medical expenses. The aim of this study is to compare postoperative hospitalization and medical expenses between patients with PRTI and non PRTI after gastrointestinal surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The main cause of SSIs is intraoperative contamination with bacteria, including intestinal flora and resident skin flora. However, most RIs are caused by cross‐infection with bacterial contaminants in the hospital environment via the hands of medical staff 17 . Studies reporting the epidemiology and influence of RIs on oncological outcomes are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause of SSIs is intraoperative contamination with bacteria, including intestinal flora and resident skin flora. However, most RIs are caused by cross‐infection with bacterial contaminants in the hospital environment via the hands of medical staff 17 . Studies reporting the epidemiology and influence of RIs on oncological outcomes are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…However, most RIs are caused by cross‐infection with bacterial contaminants in the hospital environment via the hands of medical staff. 17 Studies reporting the epidemiology and influence of RIs on oncological outcomes are scarce. Niitsuma et al 14 reported that the incidence of RI in Japanese digestive surgical patients was 3.7%, which is consistent with the result of 3.5% in our study of patients undergoing CRC surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With population aging, the proportion of older patients requiring surgery is also expected to increase (17). Postoperative complications are a significant factor determining a prolonged hospital stay, higher medical costs, and a reduced quality of life, and understanding the risks is vital for patient management (18,19). A summary of nearly 4 million gastrointestinal surgery cases using the National Clinical Database in Japan reported that complications of CDc grade III or above occurred in 3.4-21.3% of cases (20).…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of SSIs is intraoperative contamination with bacteria, including intestinal flora and resident skin flora. In contrast, most RIs are caused by cross-infection with bacterial contaminants in the hospital environment through the hands of medical staff (13).…”
Section: Definition and Epidemiology Of Surgical Site Infectionmentioning
confidence: 99%